Exploring college students' meaning of life according to Marxism in Chinese ideological and political education - Liu, Bin; Ab Razak, Ratna Roshida; Fee, Lee Yok; Md. Nor, Mohd Sabri (2024)
The research is about exploring the college student meaning of life according to Marxism in Chinese ideological and political education. For this purpose, teachers and students from 10 colleges in the region of Henan and Shanxi have been approached. The use of questionnaire with the help of SPSS-based analysis has been deployed to assessing the college students meaning of life. The significance of the concerned interventions in the case of ideological and political teaching is high and it allows the college students to diversify their position and the meaning of life is aligned accordingly. The creation of a consensus with the social change and the understanding of the ideology and class differences is associated with the students and they are aware of the situation